Asmaul Husna-based Hypnotherapyto Reduce Anxiety, Stress, and Depression in New College Student - Rohmadani, Zahro Varisna; Winarsih, Tri (Psikis : Jurnal Psikologi Islami, 2025)
Adolescence is a very important developmental period marked by significant physical, emotional, and cognitive changes, which can lead to increased susceptibility to stress, anxiety, and depression. This study aims to test the effectiveness of Asmaul Husna Hypnotherapy in reducing anxiety, stress, and depression in new students. Asmaul Husna, the 99 names of Allah, has long been known to have spiritual and psychological benefits in the Islamic tradition. One method of hypnotherapy is the Islamic hypnotherapy method. A branch of psychology known as Islamic hypnotherapy studies how suggestion can help overcome problems of thoughts, feelings, and behaviors related to Islamic values. This study used a quantitative experimental method using a control group design without treatment, involving dependent pretest and posttest samples for data collection. This study consisted of four variables, namely Asmaul Husna Hypnotherapy, depression, anxiety, and stress. The main benefit of this study is to provide a potential therapeutic alternative for individuals experiencing psychological disorders, such as depression, anxiety, and stress. The main data source in this study was the results of a questionnaire distributed to students. Data analysis was performed using an independent paired t-test. The results showed a significant decrease in the level of depression, anxiety, and stress (p <0.001) after intervention using Asmaul Husna. Husna Hypnotherapy was conducted on new students of Universitas X Yogyakarta with an average age of 19 years who initially had levels of depression, anxiety and stress in the moderate to high category, based on examinations conducted using the DASS scale (depression, anxiety scale)